Modeling local government system in Nigeria - Khalil, Samihah; Adelabu, Salihu Abdulwaheed (OMICS Group, 2011)
Local government administration is said to be the third tier of government that is closer to the people in any country amongst the three tiers of government.Nigeria is never an exemption.Today, the rate of development in Local government councils in Nigeria is geometrically based on different assessment and key performance index and economic indices within government circle.Focus, therefore should be placed on fashioning Local government administration on governance model such as what is obtained in the United States of America, United Kingdom, France, and Russia.This will eventually bring an accelerated development to the Nigerian citizens.This can easily be attained by making local government administration, a model in Nigeria.